2021
DOI: 10.1093/jpe/rtab001
|View full text |Cite
|
Sign up to set email alerts
|

Variation in regrowth ability in relation to land-use intensity in three common grassland herbs

Abstract: Aims Plant populations in managed grasslands are subject to strong selection exerted by grazing, mowing and fertilization. Many previous studies showed that this can cause evolutionary changes in mean trait values, but little is known about the evolution of phenotypic plasticity in response to land use. In this study, we aimed to elucidate the relationships between phenotypic plasticity – specifically, regrowth ability after biomass removal – and the intensity of grassland management and leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“…However, when we related our NSC storage data with regrowth data from a sister study (Kirschbaum et al 2021) we found no relationship between the two. The role of NSCs for regrowth is still subject of debate.…”
Section: Nsc Storage and Regrowth Abilitycontrasting
confidence: 58%
See 4 more Smart Citations
“…However, when we related our NSC storage data with regrowth data from a sister study (Kirschbaum et al 2021) we found no relationship between the two. The role of NSCs for regrowth is still subject of debate.…”
Section: Nsc Storage and Regrowth Abilitycontrasting
confidence: 58%
“…Finally, we tested if relative NSC content was related to the regrowth ability of P. lanceolata after a clipping treatment. For this we used data from a common garden experiment with the same plant material where we had previously tested for plasticity of regrowth ability after a clipping treatment, and had calculated plasticity as the log response ratio of clipped versus unclipped plants in terms of their total and reproductive biomass at the end of the growing season (for details see Kirschbaum et al 2021). We fitted linear mixedeffects models with plasticity of total biomass of P. lanceolata as response variable, region of origin and flowering-corrected residuals of relative NSC content as fixed effects, and population as random effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations